Strategies to load therapeutics into polysaccharide-based nanogels with a focus on microfluidics: A review. (15th August 2021) - Zoratto, N.; Montanari, E.; Viola, M.; Wang, J.; Coviello, T.; Di Meo, C.; Matricardi, P.
Abstract: Nowadays nanoparticles are increasingly investigated for the targeted and controlled delivery of therapeutics, as suggested by the high number of research articles (2400 in 2000 vs 8500 in 2020). Among them, almost 2% investigated nanogels in 2020. Nanogels or nanohydrogels (NGs) are nanoparticles formed by a swollen three-dimensional network of synthetic polymers or natural macromolecules such as polysaccharides. NGs represent a highly versatile nanocarrier, able to deliver a number of therapeutics. Currently, NGs are undergoing clinical trials for the delivery of anti-cancer vaccines. Herein, the strategies to load low molecular weight drugs, (poly)peptides and genetic material into polysaccharide NGs as well as to formulate NGs-based vaccines are summarized, with a focus on the microfluidics approach. Highlights: Strategies to load therapeutics into polysaccharide nanogels have been highlighted. The formulation of polysaccharide-based vaccines has been described. Microfluidics for facilitating the scalability of nanogel formulations has been discussed.